2002
DOI: 10.1080/08035250252833914
|View full text |Cite
|
Sign up to set email alerts
|

Does breastfeeding protect against allergic rhinitis during childhood? A meta-analysis of prospective studies

Abstract: Exclusive breastfeeding during the first 3 mo after birth protects against allergic rhinitis in children, both with and without a family history of atopy. The protective association, although of borderline statistical significance, was substantial. Larger prospective studies with strict methodology and longer periods of follow-up are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…Protection for boys did not reach statistical significance [27]. A review study indicated that exclusive breastfeeding was protective against allergic rhinitis in 3-month-old children, regardless of family history of atopy [28]. Controversy as to whether prolonged or exclusive breastfeeding protects against allergic diseases is ongoing, but breastfeeding is recommended for its protection against infections [28e31].…”
Section: Discussionmentioning
confidence: 99%
“…Protection for boys did not reach statistical significance [27]. A review study indicated that exclusive breastfeeding was protective against allergic rhinitis in 3-month-old children, regardless of family history of atopy [28]. Controversy as to whether prolonged or exclusive breastfeeding protects against allergic diseases is ongoing, but breastfeeding is recommended for its protection against infections [28e31].…”
Section: Discussionmentioning
confidence: 99%
“…9,20,62 Two systemic reviews on this subject reached the conclusion that exclusive breast-feeding does seem to have some protective effect on the development of allergy. 63,64 This effect might be due to avoidance of cow's milk protein allergen, other dietary constituents of breast milk, an immunomodulatory effect, or a combination of these. It was recently suggested that the effect of exclusive breast-feeding might be dependent on atopic heredity.…”
Section: Food Allergen Avoidancementioning
confidence: 98%
“…The formulas have equivalent nutritional values but a reduced capacity to induce IgEmediated reactions. [194][195][196][197] A large controlled study in high-risk infants using different partially and extensively hydrolyzed formulas for the first 6 months of life demonstrated that extensively hydrolyzed casein formula has the capacity to reduce AD by 50% in the first year of life. 198,199 A different approach for primary prevention is suggested by the introduction of probiotics (Lactobacillus GG) into the maternal and infantile diet.…”
Section: Potential Approaches For Primary and Secondary Prevention Of Admentioning
confidence: 99%